Overcoming Issues in Occupational Safety and Health Compliance among Contractors in Paddy and Rice Industry - Syaidan Abdullah, Muhammad; Ifwat Ahmad, Muhammad; ., . (International Journal of Engineering and Technology, 2018)
Issues related to occupational safety and health (OSH) in the agriculture sector is gaining extra attention, especially accidents that occur at workplace. This study is focusing in Selangor, Malaysia where the state shows the highest number of fatality accident rate in 2014 for this sector. The aim of this study was to propose strategies for improvement of OSH compliance among contractors in paddy and rice industry based on their main problems. A set of questionnaire was distributed to 40 registered and active contractorsâ€™ company in paddy and rice industry with a response rate was 100%. Total of 10 interview sessions were conducted in order to collect information on their issues and opinions into details. The result shows that the lack of attitude of workers towards OSH; inappropriate and inadequate of OSH training among workers; and lack of effective communication between the company and its employees were the three main problems faced by these contractors. The study was then successful in identifying the 10 main necessary steps to be taken in improving the level of OSH based on the three main problems faced by these contractors.Â